Deliberation enhances the confirmation bias in politics - David L. Dickinson (Games, 2020)
The confirmation bias, unlike other decision biases, has been shown both empirically and in theory to be enhanced with deliberation. This suggests that limited attention, reduced deliberation, or limited available cognitive resources may moderate this bias. We aimed to test this hypothesis using a validated confirmation bias task in conjunction with a protocol that randomly assigned individuals to one week of at-home sleep restriction (SR) or well-rested (WR) sleep levels. We also used a measure of cognitive reflection as an additional proxy for deliberation in our analysis. We tested the hypotheses that the confirmation bias would be stronger for WR participants and those higher in cognitive reflection on a sample of 197 young adults. Our results replicated previous findings, and both males and females separately displayed the confirmation bias. Regarding our deliberation hypotheses, the confirmation bias results were most precisely estimated for those having thought relatively more about the issue of gun control. Additionally, for the subset of individuals having thought relatively more about gun control, we found evidence that the confirmation bias was stronger for those higher in cognitive reflection and, somewhat less robustly, for those participants who were (objectively) well-rested.
Keywords: 330; cognitive reflection; confirmation bias; deliberation; sleep